Acting : the first six lessons - Boleslavsky, Richard, 1889-1937 (Theatre Arts Books, 1975)
"This classic work on acting is one of the very few that stand beside Stanislavski as a must-have for all acting students and professionals. Richard Boleslavsky's Acting: The First Six Lessons is a treasure-box of wise observation about the art of acting, all wrapped up in six charming dialogues between a teacher and a student. Generations of actors have been enriched by Boleslavsky's witty and acute picture of the actor's craft. These six "lessons" - miniature dramas about concentration, memory of emotion, dramatic action, characterization, observation, and rhythm - distill the challenge facing every actor."--BOOK JACKET.